PENGARUH ORGANIZATIONAL SILENCE (OS) TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (STUDI PADA PT INDOPRIMA GEMILANG PLANT II, SURABAYA) - RAHAYU SUSILOWATI, TRI (Jurnal Ilmu Manajemen (JIM), 2016)
A company needs employees who have well-developed hard skill and soft skill in order to give feed back to the company. The employees can give their feedback by delivering creative ideas to create new innovation and to give a progress to their company. The employees often have a hunch that silence is the best way to solve the problem. Even in Indonesia, there is a proverb related to the silence, that proverb is silence is golden. When the employees face a problem in their company, they have two alternative options: silence or speak out. However, there are a lot of employees in the company who choose the silenceoption because they assume that silence is the best way to avoid a problem. They do not realize that their silence may cause destruction of the company. The purposes of this study are to examine and analyze whether the Organizational Silence (OS) has significant effect towards the organizational citizenship behavior (OCB) (A Study in PT IndoprimaGemilang Plant II, Surabaya). This study is causality study using quantitative method. And then, probability sampling technique is used by using simple random sampling. The measurement scale used is likert scale. The result of this study shows that there is negative significant effect from the organizational silence (OS) variable towards organizational citizenship behavior (OCB) scored -3,132. Key words: organizational silence (OS), organizational citizenship behavior (OCB) Perusahaan membutuhkan karyawan yang memiliki hard skill maupun soft skill, sehingga karyawan dapat memberikan feed back (umpan balik) terhadap perusahaan. Karyawan dapat memberikan feed back dengan cara menyampaikan ide-ide kreatif mereka sehingga akan tercipta inovasi-inovasi baru, dan dapat meningkatkan kemajuan perusahaan.Karyawan seringkali beranggapan bahwa diam merupakan cara terbaik untuk menyelesaikan suatu masalah. Bahkan di Indonesia terdapat pepatah yang berkaitan dengan diam, yaitu diam adalah emas. Karyawan di dalam mengahadapi masalah yang terjadi di perusahaannya, memiliki dua alternatif untuk tetap silence atau berbicara. Akan tetapi, banyak karyawan di perusahaan yang tetap silence karena beranggapan silence adalah cara terbaik untuk menghindari suatu masalah. Karyawan tidak menyadari akibat dari silence yang terjadi, silence tersebut merupakan titik awal dari kehancuran suatu perusahaan. Tujuan dari penelitian ini adalah untuk menguji dan menganalisis apakah organizational silence (OS)berpengaruh signifikan terhadap organizational citizenzhip behavior(OCB) (Studi Pada PT Indoprima Gemilang Plant II, Surabaya). Jenis penelitian ini adalah penelitian kausalitas dengan pendekatan kuantitatif. Kemudian menggunakan teknik probability sampling, yaitu dengan sampel acak sederhana (simple random sampling).Skala pengukuran dalam penelitian ini menggunakan skala likert. The result of this study shows that there is negative significant effect from the organizational silence (OS) variable towards organizational citizenship behavior (OCB) scored -3,132. Kata Kunci : organizational silence (OS), organizational citizenship behavior (OCB)